Data-Based Maintenance Strategy Analysis using Operational Excellence Approach in Engineering Asset Management - Cahyo, Winda Nur; Prawahandaru, Haryo; Swasono, Bayu Agung; Raben, Riza Said Isyak; Sutartono, Riyan Tri; Immawan, Taufiq (International Journal of Integrated Engineering, 2019)
Traditionally, selecting maintenance strategy is based on reliability or cost. In this paper, a further discussion of redesigning the maintenance strategy is presented. The process of redesigning the maintenance strategy applies reliability centered maintenance approach and the result is analyzed further with the approach of operational excellence as presented in the structure of operational excellence. The output from the reliability centered analysis is three recommendations related to maintenance strategy. Then, the recommendations are aligned with the structure of operational excellence. The main conclusion of this study is the operational excellence approach is capable to assist the process to redesign the maintenance strategy by providing the decision maker with a guidance to improve productivity.